How organizational conditions shape development and assessment of patient-Centered lifestyle interventions targeting hard-to-reach patients with cardiac disease or type 2 diabetes - Sanne Lykke Lundstrøm; Karin Burns; Nana Folmann Hempler; Nina Ingemann Christensen; Ulla Toft; Ole Snorgaard; Louise Meinertz Jakobsen (Chronic Illness, 2026)
Objectives This study explores how organizational conditions affect the development and implementation of dialogue-based methods for patients with cardiac disease or type 2 diabetes, focusing on hard-to-reach groups. Methods Utilizing audio recordings, transcripts, and field notes from 2018-2019, we applied the Theoretical Domains Framework to analyze how individual and group processes influenced the development and implementation of initiatives. Results The study identified five key themes: environmental context and resources, social influences, skills, professional roles and identity, and optimism. A significant variation in resources and attitudes between cardiac and diabetes outpatient clinics was observed, affecting the success of dialogue-based rehabilitation strategies Cardiac nurses were more optimistic and proactive, unlike their counterparts in diabetes clinics who faced challenges related to longer disease duration and less obvious complications. Specifically, cardiac clinics had structured programs and consistent resources, while diabetes clinics faced sporadic patient engagement and limited support. Discussion The study advocates for a shift toward organizationally supported, comprehensive programs, emphasizing the need for a holistic approach in the healthcare sector to enhance the effectiveness of lifestyle interventions for chronic diseases. It further stresses the value of addressing the psychosocial factors within healthcare settings to improve patient care quality and employee well-being.